The Influence Of Jalal Al-Din Rumi’s Thoughts In Rumi Diplomacy - Alessandro Kurniawan Ulung; Clemontin Cornelia Monica Jannah (Universitas Nahdlatul Ulama Surabaya, 2023)
This study discusses the thoughts of renowned Sufi poet Jalal Al-din Rumi behind Rumi Diplomacy, rolled out by Fadjroel Rachman, Indonesian Ambassador to Kazakhstan and Tajikistan. Rumi Diplomacy takes place in a way that the ambassador uses Rumi’s works to enhance bilateral ties with Tajikistan. Rumi Diplomacy implies that the ambassador considers Rumi’s thoughts soft power in his foreign policy. This study uses a qualitative method, with the theory of foreign-policy analysis by Harold and Margaret Sprout in place. This theory enables the author to find that Rumi’s thoughts on religious moderation, universal love, and universal faith influenced Rachman’s psychological environment to perceive such thoughts as soft power to reach Indonesia’s national interests in Tajikistan. It means that he considers the development of Rumi’s influence in Indonesia as the operational environment in making his foreign policy. To identify and understand his psychological and operational environments, the author interviewed the ambassador, read Rumi’s works, and reviewed the literature. This study, which is the first to research Rumi Diplomacy, contributes to shedding light thatin international politics, literature work should not be overlooked because it can also affect the decision-making process and help a country reach national interests without coercion.